2017
DOI: 10.1111/jcpt.12599
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics and Bayesian estimation of tacrolimus exposure in Chinese liver transplant patients

Abstract: A PPK model for TAC was established successfully in Chinese liver transplant patients. POD, CLcr and ABCB1 C3435T genotypes were shown to have significant effects on CL/F. The AUC of TAC in Chinese liver transplant patients could be estimated through Bayesian modelling, based on which individualized immunosuppressive regimens can be designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
(130 reference statements)
1
26
0
Order By: Relevance
“…The best LSS (0, 2 h, 4 h) was selected using the D‐optimal design but was only evaluated in patients from the development cohort (and not an external validation cohort, which is known to highly underestimate the bias and precision) showing bias of 3.5 ± 13.8% and precision of 12.6 ± 13.9% in the estimation of AUC 0–12h. In the present study, the results of the Bayesian estimation of TAC AUC and of the dose required in the independent validation group showed that both ITSIM and Pmetrics have good predictive performance in term of bias and RMSE (<10% and <20% respectively is consensually accepted for MAP Bayesian estimation). The imprecision was overall lower in stable than in immediate post‐transplantation period for both TAC OD and TD.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…The best LSS (0, 2 h, 4 h) was selected using the D‐optimal design but was only evaluated in patients from the development cohort (and not an external validation cohort, which is known to highly underestimate the bias and precision) showing bias of 3.5 ± 13.8% and precision of 12.6 ± 13.9% in the estimation of AUC 0–12h. In the present study, the results of the Bayesian estimation of TAC AUC and of the dose required in the independent validation group showed that both ITSIM and Pmetrics have good predictive performance in term of bias and RMSE (<10% and <20% respectively is consensually accepted for MAP Bayesian estimation). The imprecision was overall lower in stable than in immediate post‐transplantation period for both TAC OD and TD.…”
Section: Discussionmentioning
confidence: 48%
“…In a previous study, we found that the same structural model also accurately described the PK of Envarsus (another once‐daily formulation of TAC) in liver transplant recipients . Several other structural models were proposed to describe the PK of TAC OD and TD in liver transplant patients . For example, Moes et al previously described the PK of TAC OD in stable liver transplant recipients using nonlinear mixed effects modelling (NONMEM).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations